Rare case of combined laryngocoele masquerading as laryngeal carcinoma: a case report and review of literature - Dwivedi, Gunjan; Gupta, Vikas; Singh, Inderdeep; Goyal, Sunil; Kumar, Manoj; Sood, Amit; Rajput, Meenakshi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Laryngocoele is an abnormal dilatation of the laryngeal saccule. It is a rare entity. Patient generally presents with hoarseness, dysphagia, dyspnea, foreign body sensation in throat and swelling in the neck. It is a benign condition, however the risk of malignancy is always associated with it, especially, if a patient is smoker or tobacco chewer. Once the diagnosis is established, laryngocoele are best treated by surgery. We present a rare case of combined laryngocoele in a 62 year old male patient, a chronic smoker, with history of recurrent swelling in neck right side for 2 years and hoarseness for duration of 1 month. It was a diagnostic dilemma as to what we were dealing with, a benign condition or malignancy. Eventually patient underwent excision by external approach. Resected specimen histo-pathological examination was consistent with laryngocoele. Post excision his normal voice was also restored.